Stick–slip behaviour on Au(111) with adsorption of copper and sulfate - Podgaynyy, Nikolay; Wezisla, Sabine; Molls, Christoph; Iqbal, Shahid; Baltruschat, Helmut (Beilstein Journal of Nanotechnology, 2015)
Several transitions in the friction coefficient with increasing load are found on Au(111) in sulfuric acid electrolyte containing Cu ions when a monolayer (or submonolayer) of Cu is adsorbed. At the corresponding normal loads, a transition to double or multiple slips in stick–slip friction is observed. The stick length in this case corresponds to multiples of the lattice distance of the adsorbed sulfate, which is adsorbed in a √3 × √7 superstructure on the copper monolayer. Stick–slip behaviour for the copper monolayer as well as for 2/3 coverage can be observed at FN ≥ 15 nN. At this normal load, a change from a small to a large friction coefficient occurs. This leads to the interpretation that the tip penetrates the electrochemical double layer at this point. At the potential (or point) of zero charge (pzc), stick–slip resolution persists at all normal forces investigated.
Keywords: AFM; friction; friction force microscopy; nanotribology; underpotential deposition